Regime de governança digital aplicada em diploma universitário com uso da blockchain - Algeri, Maria Fernanda Telles (Universidade do Vale do Rio dos Sinos, 2022)
The university diploma confers its holder the recognition of his skills and knowledge, being considered a competitive differential in the academic career and of undeniable weight in the labor market. In this scenario, given the value added to the diploma, Brazil has experienced in recent decades, persistently and exponentially, the problem of falsification of diplomas, greatly impacting the credibility of Higher Education Institutions. This leads to a necessary change in organizational culture and its systemic control. The general objective of this study is to improve the legal process of validation and trust of undergraduate diplomas through the use of Blockchain technology. The problem that the research intends to face is circumscribed to the following question: how could the University of the Rio Verde contribute to the mitigation of the fraud scenario of the diplomas it issues in favor of its graduates and of society? The hypothesis is to present the Blockchain technology as a mechanism for legal validation of diplomas, ensuring greater, speed, security, reliability, publicity and authenticity. Therefore, as specific objectives, the investigation has as research route, first, I) to understand the legal management system of certification of diplomas of the UniRV; II) to map the problem of fraud in diplomas that result in distrust as to their validity; and, III) to demonstrate the applicability of Blockchain technology as an intelligence platform in the legal validation of diplomas issued by the UniRV. The methodology used is deductive, because it will start from the analysis of the particular to impact in a generalized way the system of university organizations in the management of certification of undergraduate diplomas. The approach will be systemic-constructivist that favors the researcher the observation to propose solutions built from the experience of observing reality and building an adequate response to the problem identified. The investigation uses research techniques composed of national and foreign bibliographic references, as well as institutional data collection and analysis, therefore, of an exploratory and descriptive nature. As research findings, it was possible to verify the positive organizational impacts generated by the implementation of Digital Governance with the purpose of managing risk and feeding back trust and reputation before users, students, market and society, in general. At the end of the investigation, the initial hypothesis is confirmed in the sense that if the UniRV implements good practice guidelines in order to conform to the norms established by the MEC for the implementation of the Digital Diploma, as well as making the Blockchain technology compatible with the norms sculpted in the General Law of Data Protection, it will enable the efficiency and ethical smoothness of the application of the technology. As a substratum of the research, it is presented, at the end, a practical proposal of what was elected to call "Primer of Good Practice in the Implementation of the Digital Diploma and the Use of Blockchain Technology as a Mechanism for Legal Validation of the Diplomas Issued in the Scope of the UniRV".
Keywords: Diploma digital; Fraude; Burocratização; Governança; Blockchain; Digital diploma; Fraud; Bureaucratization; Governance; ACCNPQ::Ciências Sociais Aplicadas::Direito